2016
DOI: 10.1111/pim.12308
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response of a prostate stromal cell line induced by Trichomonas vaginalis

Abstract: While Trichomonas vaginalis, a cause of sexually transmitted infection, is known as a surface-dwelling protozoa, trichomonads have been detected in prostatic tissue from benign prostatic hyperplasia and prostatitis by immunoperoxidase assay or PCR. However, the immune response of prostate stromal cells infected with T. vaginalis has not been investigated. Our objective was to investigate whether T. vaginalis could induce an inflammatory response in prostate stromal cells. Incubation of a human prostate stromal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Although T. vaginalis infection in men has been viewed as a cause of prostatitis in clinical epidemiologic reports, certain aspects of T. vaginalis ‐induced prostatitis remain unclear. Recently, we reported that T. vaginalis induces inflammatory responses by producing inflammatory cytokines such as IL‐1β, IL‐6, CCL2, and CXCL8 in prostate epithelial and stromal cells in vitro . However, since in vitro experiments have limitations in terms of application to human diseases, animal models are needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although T. vaginalis infection in men has been viewed as a cause of prostatitis in clinical epidemiologic reports, certain aspects of T. vaginalis ‐induced prostatitis remain unclear. Recently, we reported that T. vaginalis induces inflammatory responses by producing inflammatory cytokines such as IL‐1β, IL‐6, CCL2, and CXCL8 in prostate epithelial and stromal cells in vitro . However, since in vitro experiments have limitations in terms of application to human diseases, animal models are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Male patients with chronic recurrent prostatitis and urethritis in South Korea also had a high rate (21.2%) of T. vaginalis infection . In previous studies we demonstrated that T. vaginalis induced inflammatory responses in prostate epithelial and stromal cells in vitro . Although T. vaginalis is strongly associated with inflammation of the prostate, there are obvious obstacles to carrying out in vitro experiments on the pathology of prostate disease due to T. vaginalis infection.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…They also regulate the production of pro-inflammatory cytokines by the activation of MAPK and NFκB p65 and prompt pyroptotic cell death through the release of IL-1β [36]. TLR4 upregulation has been reported in a prostate stromal cell line exposed to T. vaginalis [37].…”
Section: Other Protozoansmentioning
confidence: 99%